Who was Franklin Roosevelt? - Frith, Margaret; O'Brien, John, 1953- (New York : Grosset & Dunlap, 2010)
An illustrated biography of Franklin Delano Roosevelt that provides information on his childhood in Hyde Park, marriage to Eleanor, political career, years as president, and influence on American history.
Who was Franklin Delano Roosevelt? -- Growing up in Hyde Park -- Meeting Eleanor -- Running for office -- Facing a crisis -- Struggling to walk -- Becoming president -- Living in the White House -- Going to war -- Saying good-bye.
Includes bibliographical references (p. 104-105).
Keywords: Roosevelt, Franklin D. -- 1882-1945 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature